Dampak Implementasi Kebijakan Otonomi Daerah Terhadap Peningkatan Kualitas Pelayanan Publik (Suatu Studi Pada Dinas Kependudukan Dan Catatan Sipil Kabupaten Halmahera Utara) - Lasa, Kristovel; Pangkey, Masje Silija; Kiyai, Burhanudin (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : The research objective was to determine the impact of the implementation of the regionalautonomy policy towards improving the quality of public services in the Department of Population andCivil Registration Halmahera as Minister of State for Administrative Reform (MENPAN) No. 81/1993(Anonymous, 1993) confirms that the quality of service should be in accordance with joints as follows,simplicity, clarity and certainty, Procedures / Procedure for Public Services; Public Service requirements,both technical and Administrative; Giving Public Service; Security, Openness, Efficient, Economical,Justice Yang Evenly, and timeliness. To determine the indicator then, researchers used the method with amix of evaluative-descriptive quantitative-qualitative approach. The sample in this study consisted ofelements of employee / service personnel (n1) and the user community services (n2), each of 30 people.Given the nature of the sample is paired, then the fixed sample size of 30 people, where a sample ofemployees polled neighbor variable X, while samples of people asked their opinion of the variable Y.Based on the results of data analysis known that the hypothesis 1, which states that "Theimplementation of the regional autonomy policy impact / positive effect on improving the quality ofpublic services at the Department of Population and Civil North Halmahera District", has proven validityempirically convincingly through a simple regression analysis and predict moment correlation. As well asthe Public Services Quality Differences Between Before and After Implementation of regional autonomypolicy acceptable to convince the 99% confidence level. This means that the quality of public services atthe Department of Population and Civil Registration of North Halmahera district on the condition afterthe implementation of the regional autonomy policy is much higher than before implementation regionalautonomy policy. The results showed that the average quality of public services after the implementationof the regional autonomy policy gained an average of 56.4, or in the ideal scale test rank of 0.87, or 87%,while the condition of the quality of public services prior to the implementation of regional autonomypolicy, the average is only at 49 , 6 or the ideal measurements were obtained at 0.7631 or 76.31%, so thatthere is a difference, which is about 10.69%. It that an increase in the quality of public services after theimplementation of the regional autonomy policy, amounting to 10.69%.To improve the quality of public services that are known not optimal, it would require concertedeffort from local government districts, particularly in the Department of Population and Civil RegistrationHalmahera district North to improve human resource management and governance of public services soas to encourage the improvement of the quality of public services itself , And given the decentralizationpolicy gave the positive and significant impact on the quality of public services, local governments,particularly the Office of Population and recording of Civil North Halmahera need to deal with programsrelating to the increase in the dimensions of the regional autonomy policy, particularly the dimension ofrestructuring and revitalization organizational resources.Keywords: Impact of Regional Autonomy Policy Implementation, Improving the Quality of PublicServices.